Impact of COVID-19 on Students' Psychological Safety - Ewa CHOMAĆ-PIERZECKA; Beata Maria NOWAK; Joanna ROGOZIŃSKA-MITRUT (Communications of International Proceedings, 2022)
The outbreak of the COVID-19 pandemic has forced a number of changes in the sphere of socio-economic life. Health security, coupled with the mission of community education, has necessitated the introduction of hybrid, or remote, learning. The reorganisation of the previous education formula created a serious challenge for the staff implementing the education process, as well as for the beneficiaries of this activity, including the student community. The change in the mode of teaching has had the effect of shaking up the previous comfort level of education of individuals. New requirements, associated with increased individualism of work created a new learning environment, which shook the developed state of psychological comfort of participants in the education process. In addition, the psychological well-being of the learning community was negatively affected by the commonly reported fear for their own health and that of their loved ones, the isolation and formulaic nature of communication through available means of communication, the limited or no possibility (lockdown) of self-realisation within interest circles or recreational and sporting activities. Uncertainty about the new approach to education has reduced motivation and ambition. The authors of this paper draw attention to the problem of students' psychological safety in the reality of remote or hybrid education during the COVID-19 pandemic. They analysed the extent and strength of the impact of the pandemic on students' learning and lives. The considerations in this article are based on a review and critical appraisal of the available literature and studies together with an inference. The article is enriched by an analysis of the results of their own research into the issues explored, which takes the form of a survey.
Keywords: psychological safety; functional stability; student emotions; remote education; COVID-19.